Analisis Faktor-Faktor dan Strategi dalam Menghadapi Kredit Macet pada KSP SMP Negeri 35 Medan - Perkasa, Ripho Delzy; Dalimonte, Chairunnisa; Harahap, Fahma Amelia (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to identify the factors that cause bad credit at the SMP Negeri 35 Medan savings and loan cooperative and describe strategies for dealing with bad credit at the SMP Negeri 35 Medan savings and loan cooperative. The research method used is a qualitative descriptive method through interviews, observation, and documentation. The subjects of this research are the Chairman, Supervisory Staff, Bookkeeping Staff. The research is located on Jl. Williem Iskandar Pasar V Medan, Bandar Selamat, Kec. Medan Tembung, Medan City Prov. North Sumatra. The results of this research indicate that the factors causing bad credit at the SMP Negeri 35 Medan savings and loan cooperative are internal and external factors. The internal factors (cooperatives) consist of; cooperative officers' mistakes in analyzing potential debtors, excessive confidence, and family relationships. Meanwhile, external factors (from the customer's side) consist of need factors, the debtor's business failure (bankruptcy), and the debtor experiencing a disaster. The strategies that can be used at the SMP Negeri 35 Medan savings and credit cooperative are billing customers, communicating via telephone, and settling things amicably.